Meningioma Detection and Characterization Using Brain MR Imaging: A Case Study - Pahlivi, Riza; Abimanyu, Bagus; Jannah, Marichatul (Poltekkes Kemenkes Semarang, 2024)
Meningiomas commonly manifest as granulations, dense clusters exhibiting hyperintense signals on the meningeal layers and close to cranial nerves. Detailed and isotropic imaging are key in the diagnostic evaluation. Nevertheless, standard MRI sequences have been inadequate in capturing these granulations, incorporating the T2 3D CISS axial sequence for improved visualization. Our case study aims to meticulously evaluate the diagnostic imaging strategies used for meningioma cases, explicitly focusing on cranial nerve imaging. The MRI protocol encompassed axial, coronal, and sagittal T2_TSE and DWI sequences and post-contrast T1-weighted imaging. A detailed calibration of the 3D CISS sequence parameters was performed to enhance the imaging of cranial nerves affected by the suspected meningioma. Our findings highlight the necessity of a meticulous MRI protocol, which includes precise imaging sequences, to evaluate meningiomas effectively, particularly for assessing the potential involvement of the cranial nerves.